The Relevance of Manning’s Roughness Coefficient in Determining Hydraulic Performance of Subsurface Drainage Module - Mohd Asri, Nur Diyana (IRC, 2019)
Urbanization process is enormously affecting on the natural hydrology. It has resulted in addition of impervious area hence increasing peak flow and runoff volume. As urbanization increases, the current conventional drainage is constantly full of surface runoff hence resulting in frequent flooding. River Engineering and Urban Drainage Research Centre developed the Bio-ecological Drainage System (BIOECODS) in 2001 to reduce flooding problem by regulating the amount of stormwater runoff and preserve stormwater runoff quality. BIOECODS consist of constructed grass swales, subsurface drainage modules, dry pond, wet pond and detention pond. This study focuses on the performance of subsurface drainage modules only. Subsurface drainage modules are main component in BIOECODS technology.